2021
DOI: 10.1080/20430795.2021.1944750
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship Growth in Emerging Economies: New Insights and Approaches

Abstract: Emerging economies have a diverse range of countries regarding both geography and stage of development that have been influenced by historical, cultural, and societal change. Recently more emphasis has been placed on understanding the role of entrepreneurship in emerging economies due to changing economic conditions and the rapid rise of entrepreneurs in the global economy. This special journal issue includes a number of articles on diverse issues related to entrepreneurship in emerging economies both from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 83 publications
0
14
0
Order By: Relevance
“…They have confirmed that it is helpful at an individual level or when entrepreneurship occurs within a corporate setting (Abdelkafi and Refas, 2021). Based on that understanding, developing countries have started initiating and implementing this strategy in their search for sustainable solutions to their socioeconomic challenges (Hamdan et al, 2021). Ideally, entrepreneurial activities can help developing countries attain sustainable development goals (Abdelkafi and Refas, 2021).…”
Section: Entrepreneurship Development In Developing Countriesmentioning
confidence: 94%
“…They have confirmed that it is helpful at an individual level or when entrepreneurship occurs within a corporate setting (Abdelkafi and Refas, 2021). Based on that understanding, developing countries have started initiating and implementing this strategy in their search for sustainable solutions to their socioeconomic challenges (Hamdan et al, 2021). Ideally, entrepreneurial activities can help developing countries attain sustainable development goals (Abdelkafi and Refas, 2021).…”
Section: Entrepreneurship Development In Developing Countriesmentioning
confidence: 94%
“…The UN General Secretary put together the headings of international development and released the Millennium Development Goals (MDGs) in 2000. In these goals, which were aimed to be achieved by 2015, the headings included the following: to exterminate poverty and hunger (1), to carry into effect primary education at the international level (2), to promote gender equality and empower women (3), to decrease child mortality (4), to strengthen maternal health (5), to fight HIV/AIDS, malaria, and other diseases (6), to ensure environmental sustainability (7), and to develop global cooperation for development (8) [33].…”
Section: Un Sustainable Development Goals (Sdgs)mentioning
confidence: 99%
“…It can also be seen that they have an important role in increasing employment. Yet, today, the roles of entrepreneurs have diversified, and they have many additional purposes besides making a profit [1][2][3]. Entrepreneurs, especially in their innovative aspects, have an important effect on the world apart from economy and employment.…”
Section: Introductionmentioning
confidence: 99%
“…Entrepreneurs are now widely acknowledged as the primary force behind economic development and prosperity in developing and developed countries (Hamdan et al, 2022). Entrepreneurship also involves many significant aspects, such as increased production, productivity, level of income, healthcare system improvements, education advancements, and technological developments (Kaya et al, 2017).…”
Section: Introductionmentioning
confidence: 99%